(untitled) (Studia Prawnicze / The Legal Studies, 1990)
Trudności stosowania przepisów o rękojmi i gwarancji powodujące niejednolitość i wątpliwości praktyki mają w poważnej części swą przyczynę w pluralizmie źródeł prawa. Fakt ten utrudnia bowiem odnalezienie „normy jednostkowej” lub raczej „właściwego prawnego reżimu”, który in concreto powinien rządzić rozstrzyganym sporem. Opracowanie podejmuje dwa tylko aspekty: a) sygnalizację (opisową) wielości reżimów prawnych (rękojmia, gwarancja). Przedmiotem opisu jest tu materiał normatywny, pominięto natomiast przedstawienie podobieństw i różnic wykładni praktycznej (orzecznictwo sądowe i arbitrażowe). b) próbę wniosków praktycznych dotyczących poszukiwania in concreto „prawa właściwego” dla danego wypadku. Difficulties in the application of warranty and guarantee provisions resulting in inconsistencies and uncertainties in practice are largely caused by the plurality of legal sources. Indeed, this fact makes it difficult to find the “unitary norm” or rather the “appropriate legal regime” that in concreto should govern the dispute being decided upon. The study addresses only two aspects: a) signalling the (descriptive) pluralism of legal regimes (warranty, guarantee). The subject of the description here is the normative material, while a presentation of the similarities and differences of practical interpretation (judicial and mediation decisions) has been omitted. b) an attempt to draw practical conclusions regarding the search in concreto for the “appropriate law” for the case.